Juridical Study on the Sale of Plowing Books Through E-Marketplace Based on Positive Laws in Indonesia - Ni Nyoman Muryatini; I Gusti Agung Ayu Gita Pritayanti Dinar (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2022)
Nowadays, the rapid technological developments increasingly have an influence on changes in people’s behavior and lifestyles. The activities of offering, selling, and buying an item or even service can be done through online sites, one of which is an e-marketplace. The model of selling pirated books began to shift when the discovery of internet technology, if previously pirated books were sold at roadside stalls, but now they have developed into online sales. The convoluted process must be passed by the copyright holder if they complain about problems regarding their books being plowed and freely traded on e-marketplace. The method used in this study was a normative juridical research. Legal research was carried out to produce new arguments, theories, or even concepts as prescriptions in solving the problems. The results of the research conducted by the electronic system operator have the responsibility to follow up on any complaints or reports on the existence of electronic information or documents that are prohibited by law in their electronic system, if proven guilty, the merchant will be cut off access. In the increasingly rapid development of the world of e-commerce today, it is accompanied by the development of types of crime in the digital world, so that the urgency of regulating e-commerce specifically in a law is needed.